An analysis of household energy choice and consumption in Bauchi State, Nigeria - Danlami, Abubakar Hamid (2017)
The main choice of energy sources remains one of the most important aspects of households’ living. This study was conducted with the main aim of assessing the factors that influence household energy choice and consumption in Bauchi State, Nigeria. To achieve these objectives, samples were selected using cluster area sampling technique, whereby a total number of 539 respondents were utilised. The multinomial logit model (MNLM) result has shown that higher incomes, higher education levels, location in the urban areas and living in self – owned homes; have positive impacts on the probability of adopting cleaner sources of cooking fuel. Additionally, the estimated MNLM for the lighting fuel choice indicates that the age of the household head, the income level, location in the urban areas, the number of rooms and the availability of electricity; have positive impacts on the probability of using electricity. Furthermore, the estimated Ordinary Least Square (OLS) model indicates that gender and the number of rooms have positive impacts on firewood consumption, while the level of education and the firewood price have negative impacts on the quantity of firewood consumption. Moreover, the Tobit estimate indicates that age, income and firewood price; have positive impacts on the use of kerosene. Contrarily, kerosene price has a negative impact on the intensity of kerosene use. In addition, the OLS estimate for electricity expenditure indicates that location in the urban areas and the number of electricity devices at home; have positive impacts on the expenditure on electricity. Finally, the estimated Verme models for testing the relative income hypothesis indicate that the theory is relevant in explaining households’ energy choice and consumption. Therefore, a sound policy that will introduce some households with modern source of energy will have strong and wide impact on more households that will move towards the use of modern energy sources through the relative influence. Additionally, raising incomes and campaign awareness will help to improve the situation. Lastly, a study that will analyse household energy choice and consumption over time is recommended.